PVC (polyvinyl chloride) composition as well as preparation method and application thereof
By using specific toughening agents and Cu content controlled fillers in PVC materials, the problem of welding wires of PVC materials under high temperature conditions is solved, and low-cost, high-gloss PVC material preparation is achieved, which is suitable for a variety of application fields.
Patent Information
- Application Number
- CN202510204887.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-24
- Publication Date
- 2025-04-29
AI Technical Summary
Existing PVC materials are prone to welded wires under high temperature conditions, affecting appearance, and conventional solutions increase production costs and complexity.
By using specific types of chlorine-containing toughening agents and extremely fine particle size fillers, especially fillers with Cu content within 1500 ppm, PVC materials with low weld wires and high gloss are prepared.
It reduces or even eliminates the welding wiring problem of PVC materials, improves the gloss and appearance quality of the product, reduces production costs, and is suitable for electronics, building materials and bathrooms, household appliances and other fields.
Smart Images

Figure BDA0005284216790000101 
Figure BDA0005284216790000102 
Figure BDA0005284216790000111
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of polymer materials, and in particular to a PVC composition and a preparation method and application thereof. Background Art
[0002] Polyvinyl chloride (PVC) is a general-purpose plastic second only to polyethylene and polypropylene in the world. It is a general-purpose plastic with large output, wide application and excellent comprehensive performance. It is mixed with various additives such as stabilizers, plasticizers, fillers, etc., and then processed by plasticization and molding. Because of its advantages of flame retardancy, corrosion resistance, high hardness, light material and easy processing and synthesis, it can replace traditional stainless steel or other synthetic materials. In addition, the raw material source is abundant and the price is low. It is a general-purpose material with the best performance and price. It is widely used in instrumentation, aviation, automobiles, light industry, electronics and electrical appliances, home appliances and other fields, especially in construction or decoration of houses. Although it has the advantages of flame retardancy, high rigidity, corrosion resistance and low price, its disadvantage is that the heat deformation temperature is low, the melt softens rapidly under high temperature conditions, resulting in high melt viscosity and low melt strength. During molding, it often needs to be injected at medium and low speeds. For porous products, it is very easy to produce obvious weld lines, which greatly affects the appearance.
[0003] The conventional solution is to adjust the mold structure design, such as optimizing process parameters or mold temperature, but these are extremely demanding on the customer and increase production costs. Conventional methods such as increasing material temperature, increasing injection speed, increasing holding pressure and holding time, increasing mold temperature, reducing the amount of demoulding lubricant, and strengthening mold exhaust can reduce the weld line to a certain extent, but cannot fundamentally solve the problem.
[0004] CN104629206A discloses a spray-free PVC composition with special aesthetic effects, and its preparation method and application, comprising the following components: 70-98wt% of PVC resin; 1-25wt% of polymer-coated special effect powder microspheres; 0-10wt% of compatibilizer; 0.1-1wt% of antioxidant; 0.1-0.5wt% of processing aid; by coating the special effect powder into microspheres with an aqueous polymer dispersion and then dispersing it into the PVC resin, the compatibility of the special effect powder and the PVC resin can be significantly improved, the flow marks formed on the surface of the product during extrusion or injection molding can be eliminated, and the weld line can be reduced. The prepared spray-free PVC composition has obvious special aesthetic effects such as metallic texture and pearlescent glitter, which greatly improves the market application range of the spray-free material. However, its preparation process is complicated, the production cost is high, and it is difficult to achieve large-scale application.
[0005] Therefore, how to provide a PVC composition without weld lines, and the method is simple and universal, has become a problem to be solved urgently. Summary of the invention
[0006] In order to solve the above technical problems, the present invention provides a PVC composition and a preparation method and application thereof. By adopting a specific type of toughening agent and a filler with a specific particle size and Cu content range, a PVC material with low weld line and high gloss is obtained. There is no need to frequently change the mold structure and design, which reduces the production cost. The obtained PVC material has a good appearance and can meet the application requirements in the fields of electronics and electrical, building materials and sanitary ware, and household appliances.
[0007] To achieve this object, the present invention adopts the following technical solutions:
[0008] In a first aspect, the present invention provides a PVC composition, which comprises the following components, in parts by weight: 100 parts of PVC resin, 0.5-10 parts of chlorine-containing toughening agent, and 2.5-10 parts of filler; the D50 particle size of the filler is ≤1 μm; and the Cu content in the filler is independently ≤1500 ppm.
[0009] The PVC composition provided by the present invention comprises a base resin, a chlorine-containing toughening agent and a filler. By adopting a specific type of toughening agent and an extremely fine filler, the generation of weld lines in the PVC material is reduced, the glossiness of the product is improved, and a PVC material with good appearance is obtained. There is no need to adopt a special mold or frequently adjust process parameters, which reduces the production cost and is conducive to the commercial application of the product.
[0010] For example, the PVC resin in the present invention can be selected from commercially available products, such as Sichuan Jinlu PVC JLTS, Tianjin LG TL-700, etc.
[0011] In parts by weight, the chlorine-containing toughening agent is 0.5-10 parts, for example, it can be 0.5 parts, 1 parts, 1.5 parts, 2 parts, 2.5 parts, 3 parts, 3.5 parts, 4 parts, 5 parts, 6 parts, 7 parts, 8 parts or 9 parts.
[0012] In parts by weight, the filler is 2.5-10 parts, for example, it can be 2.5 parts, 2.8 parts, 3 parts, 3.5 parts, 4 parts, 5 parts, 6 parts, 7 parts, 8 parts or 9 parts.
[0013] The D50 particle size of the filler is ≤1 μm, for example, it can be 0.9 μm, 0.8 μm, 0.7 μm, 0.6 μm, 0.5 μm, 0.3 μm, 0.1 μm, 0.05 μm or 0.01 μm, etc. Considering the cost and dispersibility, the particle size of the filler is ≥0.3 μm.
[0014] In the present invention, the D50 particle size of the filler can be tested by a laser particle size analyzer method in the calcium carbonate analysis and detection method in GB / T19281-2014.
[0015] For example, the filler in the present invention can be selected from commercially available products, such as AC-MLT04, IMIFABI, HTPULTRA5L of Melitate, etc., or the filler can be obtained by processing the above commercially available products.
[0016] The content of Cu in the filler is ≤1500ppm, for example, it can be 1400ppm, 1300ppm, 1200ppm, 1100ppm, 1000ppm, 900ppm, 800ppm, 700ppm, 600ppm, 500ppm, 300ppm, 100ppm, 50ppm or 10ppm, etc. Considering the purification cost and instrument detection sensitivity, the content of Cu in the filler is independently ≥20ppm.
[0017] In the present invention, when the content of Cu in the filler is within the above range, the obtained PVC composition has fewer weld lines and higher product gloss; the reason is that when the Cu content is within a specific range, the adsorption of Cu on other components in the PVC composition can be inhibited, the dispersibility of the PVC melt can be improved, and the overall stability of the PVC can be improved, the degree of the material weld line can be improved, and a PVC product with a better appearance can be obtained.
[0018] In the present invention, the content of Cu is obtained by ICP (inductively coupled plasma emission spectrometer) testing.
[0019] In the present invention, in order to obtain a filler with a low impurity content, the Cu content therein can be reduced by post-treating the commercial filler. For example, the heavy metal scavenger JCET-1 can be used to remove copper. The specific method includes: mixing a filler suspension or solution containing copper ions with a heavy metal scavenger, stirring sufficiently to allow the copper ions to be adsorbed onto the surface of the adsorbent, separating the heavy metal scavenger from the filler by filtering, centrifuging, etc., washing and drying the filler to obtain a filler with a specific Cu content; wherein the heavy metal scavenger can be regenerated or discarded.
[0020] Preferably, the degree of polymerization of the PVC resin is 400-1100, for example, 450, 500, 550, 600, 650, 700, 750, 800, 850, 900, 950, 1000, 1050, 1100, etc.
[0021] Preferably, the chlorine-containing toughening agent includes a chlorinated polyethylene (CPE) toughening agent.
[0022] For example, the chlorine-containing toughening agent in the present invention can be selected from commercially available products, such as CPE-132C and CPE-6325C produced by Hangzhou Keli.
[0023] Preferably, the mass content of chlorine in the chlorine-containing toughening agent is 30-40%, for example, it can be 30.5%, 31%, 31.5%, 32%, 32.5%, 33%, 34%, 36%, 38%, 40%, etc.
[0024] As a preferred technical solution of the present invention, the use of a chlorine-containing toughening agent with a high chlorine content is beneficial to improving the compatibility of the toughening agent with the PVC matrix, further reducing the generation of weld lines, and at the same time improving the gloss of the product.
[0025] In the present invention, the mass content of chlorine is tested according to the reference standard ISO7725.
[0026] Preferably, the filler includes any one of calcium carbonate, titanium dioxide or talc, or a combination of at least two of them, and calcium carbonate is more preferred.
[0027] Preferably, the PVC composition further comprises 0.1-105 parts of ABS resin (acrylonitrile-butadiene-styrene terpolymer) by weight, for example, 0.5 parts, 1 parts, 5 parts, 10 parts, 20 parts, 30 parts, 40 parts, 50 parts, 60 parts or 70 parts, etc., more preferably 30-80 parts.
[0028] As a preferred technical solution of the present invention, the PVC composition also includes ABS resin. ABS resin has higher thermal stability and better toughness than PVC. The alloy material formed by the two has excellent mechanical strength, which not only enhances the toughness of PVC, but also increases the heat deformation temperature of PVC, thereby expanding the application field of PVC.
[0029] Preferably, the melt index of the ABS resin under the test conditions of 220° C. and 10 kg weight is ≥45 g / 10 min, for example, it can be 50 g / 10 min, 55 g / 10 min, 60 g / 10 min, 70 g / 10 min, 80 g / 10 min, 90 g / 10 min or 100 g / 10 min.
[0030] Preferably, the PVC composition further comprises 2-5 parts of stabilizer by weight, for example, 2.5 parts, 3 parts, 3.5 parts, 4 parts or 4.5 parts.
[0031] Preferably, the stabilizer comprises an organotin stabilizer.
[0032] Preferably, the mass content of tin in the organotin stabilizer is ≥19%, for example, it can be 20%, 25%, 30%, 35%, 40%, 50%, 60%, 70%, 80% or 90%.
[0033] Preferably, the organotin stabilizer includes any one of methyltin mercaptan, butyltin mercaptan, di-n-octyltin dilaurate or di-n-octyltin maleate, or a combination of at least two thereof.
[0034] For example, the stabilizer in the present invention can be selected from commercially available products, such as Yunnan Tin Industry YT-181.
[0035] Preferably, the PVC composition further comprises 1-3 parts of lubricant by weight, for example, 1.2 parts, 1.5 parts, 1.8 parts, 2 parts, 2.2 parts, 2.5 parts or 2.8 parts.
[0036] Preferably, the lubricant comprises polyethylene wax and / or oxidized polyethylene wax.
[0037] For example, the lubricant in the present invention can be a commercially available product, such as Honeywell 316A, 617A, etc.
[0038] In a second aspect, the present invention provides a method for preparing the PVC composition according to the first aspect, characterized in that the preparation method comprises the following steps:
[0039] The PVC resin, the chlorine-containing toughening agent, the filler, the optional ABS resin, the optional stabilizer, and the optional lubricant are mixed, extruded and granulated to obtain the PVC composition.
[0040] Preferably, the mixing comprises heating and mixing the PVC resin, the stabilizer and the lubricant, and then adding the ABS resin, the chlorine-containing toughening agent and the filler and mixing them evenly to obtain a mixed powder.
[0041] Preferably, the temperature of the heating and mixing is 90-150°C, for example, 95°C, 100°C, 110°C, 120°C, 130°C or 140°C.
[0042] Preferably, the heating and mixing time is 5-12 min, for example, 6 min, 7 min, 8 min, 9 min, 10 min or 11 min.
[0043] Preferably, the mixing time is 1-5 min, for example, 1.5 min, 2 min, 2.5 min, 3 min, 3.5 min, 4 min or 4.5 min.
[0044] Preferably, after the mixing, the mixed powder is cooled and extruded into granules.
[0045] Preferably, the cooling temperature is 60-90°C, for example, 65°C, 70°C, 75°C, 80°C or 85°C.
[0046] Preferably, the temperature of the extrusion granulation is 140-180°C, for example, 145°C, 150°C, 155°C, 160°C, 165°C, 170°C or 175°C.
[0047] Preferably, the extrusion granulation is carried out in a screw extruder.
[0048] Preferably, the aspect ratio of the screw extruder is (20-40):1, wherein the specific value of (20-40) can be, for example, 22, 25, 28, 30, 32, 35 or 38.
[0049] Preferably, the screw speed of the screw extruder is 100-200 rpm, for example, it can be 110 rpm, 130 rpm, 150 rpm, 170 rpm or 190 rpm.
[0050] Preferably, the preparation method comprises the following steps:
[0051] PVC resin, stabilizer and lubricant are added into a high-speed mixer, heated and mixed to 90-150° C., ABS resin, chlorine-containing toughening agent and filler are added, mixed for 1-5 minutes, the mixed powder in the high-speed mixer is discharged into a low-speed mixer, cooled to 60-90° C., the mixed powder is fed into the extruder screw for die surface hot cutting granulation, cooled in a dehydrator, and separated by a vibrating screen to obtain the PVC composition.
[0052] The granular material prepared by the present invention can be injection molded in a designated mold under a standard process to obtain a desired product.
[0053] Exemplarily, the standard process may be that the injection speed of this injection molding process is 50%, the injection pressure is 70%, the melting speed is 50%, the melting pressure is 70%, the holding speed is 40%, the holding pressure is 50%, the injection time is 3.5s, and the cooling time is 10s.
[0054] The unit "%" of speed and pressure refers to the upper limit value of the machine parameter.
[0055] In a third aspect, the present invention provides a use of the PVC composition as described in the first aspect in electronic and electrical products, building materials, sanitary ware or household appliances.
[0056] Compared with the prior art, the present invention has at least the following beneficial effects:
[0057] The PVC composition provided by the present invention reduces or even eliminates the weld line problem of the PVC material by adopting a specific type of toughening agent and a filler with a specific particle size and a Cu content range, thereby obtaining a PVC material with high gloss and good appearance, which can meet the application requirements in the fields of electronics, building materials, sanitary ware, household appliances, etc.; the present invention optimizes the composition of PVC, and the method is simple and universal, so there is no need to replace the mold structure or accurately adjust the process parameters during production, thereby reducing the production cost and facilitating its commercial application. DETAILED DESCRIPTION
[0058] For the convenience of understanding the present invention, the present invention lists the following embodiments. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0059] In the following specific implementation of the present invention, the materials involved are as follows:
[0060] (1) PVC resin
[0061] Tianjin LG PVC TL-700, with a polymerization degree of 700;
[0062] Tianjin LG PVC TL-1000, degree of polymerization is 1000.
[0063] (2) Toughening agent
[0064] CPE toughening agent 1, Hangzhou Keli CPE-132C, the mass content of chlorine is 32%;
[0065] CPE toughening agent 2, Hangzhou Keli CPE-6325, the mass content of chlorine is 35%;
[0066] Methyl methacrylate-butadiene-styrene terpolymer (MBS), Japan Kabushige B625, the mass content of chlorine is 0%.
[0067] (3) Filling
[0068] Calcium carbonate-d1: D50 particle size is 0.8 μm, Cu content is 2000 ppm, AC-MLT04 purchased from Melite is ground to an average particle size of 0.8 μm, and then a heavy metal scavenger JCET-1 is used to remove part of the copper to obtain it.
[0069] Calcium carbonate-d2: D50 particle size is 1.55 μm, Cu content is 1200 ppm, AC-MLT04 purchased from Melite is obtained by removing part of copper through heavy metal scavenger JCET-1.
[0070] Calcium carbonate 1: D50 particle size is 0.8 μm, Cu content is 1200 ppm, AC-MLT04 purchased from Melite is ground to a D50 particle size of 0.8 μm, and then a heavy metal scavenger JCET-1 is used to remove part of the copper to obtain the calcium carbonate 1.
[0071] Calcium carbonate 2: D50 particle size is 0.5 μm, Cu content is 850 ppm, AC-MLT04 purchased from Melite was ground to a D50 particle size of 0.5 μm, and then a heavy metal scavenger JCET-1 was used to remove part of the copper to obtain the calcium carbonate 2.
[0072] Talc powder, with a particle size of 0.5 μm and a Cu content of 850 ppm, is obtained by grinding talc powder purchased from IMIFABI, HTPULTRA5L to a D50 particle size of 0.5 μm, and then using a heavy metal scavenger JCET-1 to remove part of the copper.
[0073] (4) ABS resin
[0074] LG, ABS HP181, melt index at 220°C, 10kg weight test conditions is 52g / 10min.
[0075] (5) Stabilizer
[0076] Methyltin mercaptan, Yunnan Tin Industry YT-181.
[0077] (6) Lubricant
[0078] Polyethylene wax, Honeywell 316A.
[0079] Example 1
[0080] A PVC composition, which comprises, by weight, 100 parts of PVC resin (Tianjin LG PVC TL-700), 3 parts of CPE toughening agent (CPE-132C), 13 parts of filler calcium carbonate, 10 parts of ABS resin, 2 parts of stabilizer methyl tin mercaptan, and 1 part of lubricant polyethylene wax;
[0081] The PVC composition is prepared by the following method:
[0082] Weigh PVC resin, stabilizer, and lubricant, add them into a high-speed mixer, heat and mix them to 100° C. for 10 minutes, add ABS resin, toughening agent, and filler, mix for 3 minutes, discharge the mixed powder in the high-speed mixer into a low-speed mixer, cool to 80° C., feed the mixed powder into the extruder screw for die surface hot cutting granulation, cool to 100° C. in a dehydrator, and separate on a vibrating screen to obtain the PVC composition;
[0083] Among them, the screw barrel for hot-cut granulation of the die surface has nine sections, and the screw barrel temperatures are 140℃-140℃-150℃-150℃-160℃-160℃-170℃-170℃-170℃; the extruder screw has a length-to-diameter ratio of 36:1, a main machine current of 45%, and a rotation speed of 150rpm.
[0084] The following performance tests were performed on the PVC composition provided in Example 1:
[0085] (1) Weld line extent
[0086] The prepared granular PVC composition was injection molded to obtain a switch panel socket, and the welding line was tested. The injection molding conditions were: the injection molding machine was Zhenxiong 80T, EM80-V, the temperature was 175°C, the speed and pressure were 50% and 65% respectively (where "%" refers to the upper limit value of the machine parameters), the mold temperature was 40°C, and a porous irregular sample was obtained with a length and width of about 65mm×40mm.
[0087] The highlight surface of the switch panel socket was observed using a Leica optical microscope. The “-” represents a unit of weld line length. The more -s there are, the longer the weld line is and the worse the effect is.
[0088] (2) Glossiness
[0089] The product gloss 60° is obtained by referring to the test method ASTM D2457.
[0090] The test results are summarized in Table 1.
[0091] Examples 2-11, Comparative Examples 1-6
[0092] A PVC composition, which is different from Example 1 in that the formula of the PVC composition is different, as shown in Tables 1 and 2; wherein the dosage unit of each component is "parts by weight" of the solid content; and the preparation method and performance testing method of the PVC composition are the same as those of Example 1.
[0093] Table 1
[0094]
[0095] Table 2
[0096]
[0097]
[0098] It can be seen from the test results that the present invention significantly reduces the weld line of the PVC material by adopting a specific type of toughening agent and a filler with a specific particle size range and Cu content. The method is simple and universal, and a PVC material with good appearance can be obtained, which meets the application needs in the fields of electronics and electrical, building materials and sanitary ware, and household appliances.
[0099] By comparing Example 4 with Example 5, it can be seen that the present invention improves the fluidity of the resin matrix by limiting the polymerization degree of the PVC resin, so that the melt is well dispersed and not easy to aggregate, thereby reducing the generation of weld lines.
[0100] By comparing Example 4 with Examples 6, 7 and 9, it can be seen that the present invention is beneficial to the melt dispersion of the PVC composition by adjusting the amount of ABS resin, thereby further reducing the weld line in the product.
[0101] By comparing Example 4 with Example 10, it can be seen that the present invention can improve the overall stability of PVC by optimizing the type of filler, further improve the degree of material weld line, and obtain a PVC product with better appearance.
[0102] By comparing Example 4 with Comparative Examples 1-3, it can be seen that the present invention significantly reduces the weld lines in the product obtained from the PVC composition by limiting the amount of toughening agent and filler in the PVC composition; by comparing Example 4 with Comparative Example 4, it can be seen that the particle size is conducive to the probability of disordered flipping of each component, reducing the degree of weld marks, and when the particle size of the filler used is relatively large, the weld line in the product obtained from the PVC composition is obvious and the gloss is low; by comparing Example 4 with Comparative Example 5, it can be seen that when the toughening agent does not contain chlorine, its compatibility with the PVC matrix is poor, resulting in deterioration of melt uniformity, which in turn leads to obvious weld lines and decreased gloss in the product obtained from the PVC composition, which is difficult to meet application requirements; by comparing Example 4 with Comparative Example 6, it can be seen that the present invention inhibits the adsorption of Cu on other components in the PVC composition by optimizing the Cu content in the filler, improves the dispersion of the PVC melt, improves the overall stability of the PVC, further improves the degree of material weld lines, and obtains a PVC product with better appearance.
[0103] The applicant declares that the above is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention shall fall within the protection scope and disclosure scope of the present invention.
Claims
1. A PVC composition, characterized in that: The PVC composition comprises the following components in parts by weight: 100 parts of PVC resin, 0.5-10 parts of chlorine-containing toughening agent, and 2.5-10 parts of filler; The D50 particle size of the filler is ≤1 μm; The content of Cu in the filler is independently ≤1500 ppm.
2. The PVC composition according to claim 1, characterized in that The polymerization degree of the PVC resin is 400-1100.
3. The PVC composition according to claim 1, characterized in that The chlorine-containing toughening agent includes a chlorinated polyethylene toughening agent; Preferably, the mass content of chlorine in the chlorine-containing toughening agent is 30-40%.
4. The PVC composition according to claim 1, characterized in that The filler includes any one of calcium carbonate, titanium dioxide or talcum powder or a combination of at least two thereof, preferably calcium carbonate.
5. The PVC composition according to claim 1, characterized in that In parts by weight, the PVC composition further comprises 0.1-105 parts of ABS resin, more preferably 30-80 parts; Preferably, the melt index of the ABS resin under the test conditions of 220° C. and 10 kg weight is ≥45 g / 10 min.
6. The PVC composition according to claim 1, characterized in that The PVC composition further comprises 2-5 parts of a stabilizer by weight; Preferably, the stabilizer comprises an organotin stabilizer; Preferably, the mass content of tin in the organic tin stabilizer is ≥ 19%.
7. The PVC composition according to claim 1, characterized in that The PVC composition further comprises 1-3 parts of lubricant in parts by weight; Preferably, the lubricant comprises polyethylene wax and / or oxidized polyethylene wax.
8. A method for preparing the PVC composition according to any one of claims 1 to 7, characterized in that: The preparation method comprises the following steps: The PVC resin, the chlorine-containing toughening agent, the filler, the optional ABS resin, the optional stabilizer, and the optional lubricant are mixed, extruded and granulated to obtain the PVC composition.
9. The preparation method according to claim 8, characterized in that: The mixing comprises heating and mixing PVC resin, stabilizer and lubricant, and then adding ABS resin, chlorine-containing toughening agent and filler to mix well to obtain mixed powder; Preferably, the temperature of the heating and mixing is 90-150°C; Preferably, the heating and mixing time is 5-12 minutes; Preferably, the mixing time is 1-5 min; Preferably, after the mixing, the mixed powder is cooled and extruded into granules; Preferably, the cooling temperature is 60-90°C.
10. Use of the PVC composition according to any one of claims 1 to 7 in electronic and electrical products, building materials, sanitary ware or household appliances.
Citation Information
Patent Citations
Spraying-free PVC composition having special aesthetic effects and preparation method and application thereof
CN104629206A